Entre Rhône et Rhin : les ports fluvio-lacustres de la Suisse romaine - Romain Guichon (Gallia)
This article provides an updated presentation of discoveries related to Roman riverbank installations and port structures identified in present-day Switzerland. About twenty sites are taken into consideration between Lake Geneva and Lake Constance. The typological description of the structures is privileged, as well as their position relative to surrounding towns and territories. The importance of the hydrographic context between the Rhône and Rhine river basins, as well as the regional fluvio-lacustrine transport network is also underscored. These various ports structures are in urban (Geneva, Lausanne), peri-urban (Avenches, Solothurn, Windisch) or rural (Rolle, lower-Broye) contexts. Rivers and lakes shores are most frequently reinforced with oak piles and stone embankments. Some quays are also arranged as wooden plank platforms possibly linked with storage areas. At least four large piers are attested in Geneva, Lausanne and Avenches, in connection with the early road networks of roman cities. Other atypical arrangements such as the monumental composite dike at the fluvial harbour of Studen “Wydenpark” are also documented. A spotlight is shone on the excavations carried out between 2016 and 2018 at Lausanne “Olympic House”. This work allowed for the exploration of nearly 8.000 m2 and revealed various distinct zones of a vicus port district in Lausanne/Lousonna (Vidy). The numerous structures dated between the end of the 1st c. BC and the 4th c. AD (wooden banks, docks, piers, warehouses, etc.) synthesize many of the characteristics identified at the regional scale. This exceptional site also allows to study for the first time in Switzerland the three theoretical spaces of an ancient port, as they were redefined during the Nantes conference (navigation, loading-unloading, storage).